Association of hTERT expression, Her2Neu, estrogen receptors, progesterone receptors, with telomere length before and at the end of treatment in breast cancer patients - Murillo-Ortiz, Blanca Olivia; García-Corrales, Kenia; Martínez-Garza, Sandra; Romero-Vázquez, Marcos Javier; Agustín-Godínez, Eduardo; Escareño-Gómez, Andrea; Silva-Guerrero, Daniela Guadalupe; Mendoza-Ramírez, Saulo; Murguia-Perez, Mario (Frontiers in Medicine, 2024)
Background: The aim of this study was to detect the expression of hTERT, estrogen receptor (ER), progesterone receptor (PR), and HER2-Neu in neoplastic breast tissue embedded in paraffin before treatment and to investigate the relationship between them and with baseline and posttreatment telomere length, as well as with various clinicopathological parameters.: A cross-sectional-correlational, 21 women diagnosed with breast cancer at the Oncology Service of the High Specialty Medical Unit No. 1 of Bajio of the Mexican Institute of Social Security. A peripheral blood sample was obtained before oncological treatment and at the end of oncological treatment for the measurement of telomere length by extracting DNA from leukocytes, was performed by the quantitative polymerase chain reaction (PCR) method described by Cawthon. Tumor samples were collected from each patient at the oncology department for immunohistochemical determination of biomarker expression (ER, PR, Her2/neu) and hTERT.Results: Of the 21 cases included in the study, the median age was 57.57 years. Eighteen cases were classified as invasive ductal carcinoma NOS (85.71%), 10 were histologic grade 2 (47.61%), 16 cases were hormone receptor positive (76.19%), 7 were Her2Neu positive (33.33%), and only 2 cases were triple negative (9.52%). Positive hTERT expression was detected in 11 cases (52.38%) and was negative in the remaining cases. A significant association was identified between hTERT-positive cases and Her2-Neu positive cases (p=0.04). Baseline and post-treatment telomere lengths showed a significant difference using the non-parametric Wilcoxon t-test (p=0.002). In hTERT-positive cases, there was significant telomere shortening at the end of oncological treatment (6.14 ± 1.54 vs. 4.75 ± 1.96 Kb, p=0.007).Positive hTERT immunostaining cases were associated with poor prognostic factors, such as Her2-Neu overexpression and post-treatment telomere shortening. In the future, hTERT immunostaining could be used to select patients for therapies with antagonistic effects on hTERT, as well as in the selection of more appropriate chemotherapy regimens for patients who express it.